The Analysis of How Apnea Influences the Autonomic Nervous System Using Short-Term Heart Rate Variability Indices. (19th December 2020) - He, Baolin; Li, Wenyu; Zhang, Xiaotong; Wu, Yanan; Liu, Jing; Brewer, Lara M.; Yu, Lu
Abstract : Objective . Frequent cessations of respiration can greatly increase the prevalence rate of arrhythmia. It has been confirmed that cardiac modulation is regulated by the autonomic nervous system (ANS). And heart rate variability (HRV) is widely used as a method to evaluate the function of the ANS. Therefore, we analyzed whether apnea can affect the balance and normal function of the ANS using short-term HRV indices. Methods . Forty-five healthy subjects were asked to breathe normally and hold their breathing to simulate 10 times apnea. Thirty-six patients from the dataset of a sleep laboratory for the diagnosis of sleep disorders with 10 times apnea were included in analysis. We calculated short-term HRV indices of subjects in normal respiratory and apneic states, respectively. Results . Compared with the normal respiratory state, respiration cease would lead to the values of Mean-RR, nLF, LF/HF, and α 1 which significantly increased, whereas the values of rMSSD and nHF significantly decreased. Conclusions . Cessations of respiration would lead to an imbalance in the function of the ANS, as well as an increase in fractal characteristics of the heart. These changes in the physiological state are likely to induce and cause the occurrence of arrhythmia, which is regulated by the ANS.